A comparative analysis of second-generation biofuels and its potentials for large-scale production in arid and semi-arid regions. (1st July 2023) - Makkawi, Yassir; Khan, Muhammad; Pour, Fatemeh Hassan; Moussa, Omar; Mohamed, Baraa; Alnoman, Hamza; Elsayed, Yehya
Graphical abstract: Highlights: The potential of second-generation biofuels from eight different feedstock is assessed. Food waste is an ideal feedstock for biofuel in arid and semi-arid regions. All biochar, except that from biosolids, are stable for long-term carbon sequestration. Digested sewage sludge produces gas with the highest heating value (∼39 MJ kg −1 ). Co-feeding is highly recommended for the implementation of large-scale processing. Abstract: This study compares the pyrolysis products from eight different feedstocks of potential availability in arid and semi-arid regions, namely, post-consumption food waste, biosolids (anaerobically digested and undigested sewage sludges), segregated fruits and vegetable waste, animal manure, date palm waste, and halophyte plant ( Salicornia bigelovii seed and seedless-plant). Food waste, Salicornia bigelovii seed, and undigested sludge produced the highest bio-oil yield, 38.0 %, 35.3 %, and 32.5 %, respectively. The bio-oils from food waste and Salicornia bigelovii seed were rich in acidic compounds. The former has the highest calorific value (34.7 MJ kg −1 ), while the latter is the lowest due to a significant amount of water (29.9 mass%). The biosolids produced bio-oil rich in alcohols and esters, turning it towards high alkalinity (pH > 9). The biochar from animal manure and biosolids has the lowest calorific value (<10.0 MJ kg −1 ) and the least potential for soil amendment and carbon sequestration due to poor stability, low fixed carbon, and significantly high ash content in the feed (>39 mass%). The gas from digested biosolid has the highest calorific value (>38.9 MJ kg −1 ), benefiting from the presence of high H2 content (21.2 mass%). Analysis of the potential implementation of the eight feedstocks for pyrolysis in an arid region indicates that food waste is the most promising due to its superior bio-oil quality, higher conversion efficiency, abundant availability, and the possibility of low-cost drying.